2021
DOI: 10.3390/ma14226822
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Process Parameters on Grain Size and Texture Evolution of Fe-3.2 wt.-% Si Non-Oriented Electrical Steels

Abstract: The magnetic properties of non-oriented electrical steel, widely used in electric machines, are closely related to the grain size and texture of the material. How to control the evolution of grain size and texture through processing in order to improve the magnetic properties is the research focus of this article. Therefore, the complete process chain of a non-oriented electrical steel with 3.2 wt.-% Si was studied with regard to hot rolling, cold rolling, and final annealing on laboratory scale. Through a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In order to create such a tailor-made material or microstructure, the requirements of the electrical machine, the influence of different material properties on different loss components and how to adjust these properties accordingly along the process chain (see [ 4 ] for more details) need to be known. Behind all this knowledge are the characterization methods.…”
Section: Introduction—characterization As the Basis For Tailor-made Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to create such a tailor-made material or microstructure, the requirements of the electrical machine, the influence of different material properties on different loss components and how to adjust these properties accordingly along the process chain (see [ 4 ] for more details) need to be known. Behind all this knowledge are the characterization methods.…”
Section: Introduction—characterization As the Basis For Tailor-made Materialsmentioning
confidence: 99%
“…Thereby, every publication focuses on a different aspect of this material. Two papers revolve around processing and its influence on microstructure, texture and magnetic properties [ 4 , 5 ]; one deals with integrated process simulation [ 6 ] and the last with material design [ 3 ], all drawing heavily on experimental results from the established and advanced methods described and discussed here. In the current paper, we present the key methods for fully characterizing the most important properties of electrical steel.…”
Section: Introduction—characterization As the Basis For Tailor-made Materialsmentioning
confidence: 99%
“…Hot rolling, cold rolling and annealing resulted in six different types of electrical steel sheets with distinct average grain sizes. The hot rolling, cold rolling and annealing process for the investigated materials is described in detail in [18]. Grain size measurement by the line intercept method in the rolling direction and the transverse direction was realized in the surface plane of the sheets at around 90% sheet thickness and in the mid layer at around 50% sheet thickness.…”
Section: Chemicalelementmentioning
confidence: 99%
“…The influence of the cold rolling degree and the annealing temperature on the texture and grain size of the blanked steel sheets was evaluated by Wei et al [18]. It was shown that the applied annealing temperature has a rather strong effect on texture compared to the cold rolling degree.…”
Section: Influence Of Texturementioning
confidence: 99%
“…Magnetic properties are the most required performances of NOE steels and are mainly affected by the composition of the steel especially the contents of aluminum and silicon, [1,2] the microstructure namely the grain size and textures, [3,4] the impurities mainly including second-phase inclusions and residual harmful elements, [5][6][7][8] and the rolling and annealing process parameters. [9][10][11][12] Second-phase inclusions especially nanodiameter sulfides can retard the migration of grain boundaries by Zener force, causing fine grain size and unfavorable textures, which were harmful to magnetic properties. [13][14][15] In addition, fine sulfides can also hinder the movement of domain walls during the magnetization process, causing an increase in coercivity force, [16] which leads to an increase in the core loss of NOE steels.…”
Section: Introductionmentioning
confidence: 99%